Enema em equinos saudáveis: avaliação clínica e laboratorial. - Ubiratan Pereira de Melo (2007)
The effect of three different enema solutions was studied on clinical, homeostatic, hematological, and biochemistry parameters of equines, as well as the effect in macro and microscopic characteristics of distal small colon and rectum mucosas. Fifteen healthy adult animals were pooled according to weight and gender (four females and one male per group) and distributed into three groups (five equines per each), as the following: group 1 tap water associated with neuter soap; group 2 isotonic solution; and group 3 tap water associated with vaseline. The type of enema solution influenced on the forecited parameters. Isotonic solution caused less alteration on the parameters of colon mucosa. Tap water and neuter soap induced metabolic alkalosis, decrease in electrolytes concentration, and inflammatory reaction on colon mucosa. Even though all three solutions showed effectiveness in hydrating and softening the feces, water with soap solution presented the best results.